Book review by Bazyli Czyżewski ”Economic rents in Poland’s food economy” - Poczta, Walenty (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
Book review by Bazyli Czyżewski ”Economic rents in Poland’s food economy”. Polskie Wydawnictwo Ekonomiczne, Warszawa, 2013, s. 447.